Ivorite to Rathrapage: Challenges of Democratisation in Cote d’Ivoire - Agunbiade, Doyinsola (Advances in Social Sciences Research Journal, 2026)
Attacks from a variety of current and new threats have increased, changing the relative stability that existed in West Africa after a period of brutal and protracted conflicts in the 1990s. Studies have majorly looked into the nature, causes, consequences, challenges of post-conflict peace-building process, sustenance of the post-conflict peace process, weak state and its conflict dilemma, lessons learnt from peace-building process, interventions that led to the cessation of hostilities between the parties to the conflict in the country (Yere, 2007; Owusu-Sekyere, 2009; Langer, 2010) while little attention has been given critiquing and rethinking the concept of identity conflict within the narrative of democratisation in Cote d’Ivoire. Using the 2015 and 2020 elections in Cote d’Ivoire as case studies, this paper explores the electioneering process as one of the critical markers of democracy and addressing issues of identity within the context of democratisation. In this paper, efforts have been made to draw upon what has been the event in the last forty years and attempting to clarify what is temporary and what is permanent, what is important and what is superficial in recent Ivorian electioneering process and democratic system in place. The historical trend around issues of identity conflict in Cote d’Ivoire has shaped and introduced some dynamics and thoughts on democratisation. This paper therefore was designed to critique and rethink the concept of identity conflict within the broader narrative of nationality and democratisation in Cote d’Ivoire. While a case study research design was adopted, Primary and secondary data were obtained as well as Key informant interviews with stakeholders. The concept of rathrapage is fundamental to the contestations around identity conflict. These arguments indicate a need to reconsider familiar tropes of identity and institutions and the way we think about democratic elections and violent conflicts in Cote d’Ivoire.